The Impact of Microfinance Banks on the Growth of Small and Medium Enterprises in Lagos Metropolis - Aladejebi, Olufemi (European Journal of Sustainable Development, 2019)
Small and Medium Enterprises (SMEs) play a major role in the Nigerian economy, especially in terms of Employment, growth, productivity, and poverty alleviation. The purpose of this study was to examine the impact of Microfinance Banks (MFB) on the growth of SMEs in Lagos metropolis The data for this study was collected via questionnaires given to the owners of SMEs that had accounts with microfinance banks in Lagos metropolis. Out of 209 questionnaires distributed, 205 were viable and analyzed using the SPSS package. The questionnaire contained 2 sections. Section 1 for general information while section 2 contains questions on effects of micro-savings on financial performance, effects of microcredit on the financial performance of the SMEs, effects of training on the financial performance of the SMEs and financial performance. The outcome revealed that the savings among SMEs are encouraging because of higher interest rates compared to deposit banks, faster loan disbursement, failure of MFBs to conduct training for SMEs, while the majority of SMEs experienced financial growth using MFB products. Keywords: Small business, Microfinance banks, SME growth, Lagos metropolis